The Implementation of Pancasila Student Profile Strengthening Program in Pioneer Elementary Schools - Fathiyah Indah; Muhson, Ali (Journal of Education Reseach and Evaluation, 2025)
The Pancasila Student Profile Strengthening Project (P5) is designed to shape students' character; however, the consistent implementation of P5 principles still faces various challenges. This study aims to evaluate the P5 program in elementary schools to assess the program's relevance and quality in supporting P5 objectives. This evaluative research employs a quantitative descriptive approach using the Countenance Stake model. The study involved 5 principals, 30 teachers, and 122 students from driving elementary schools selected through purposive sampling. Data were collected through questionnaires and document analysis. Prior to the evaluation, a P5 Phase B student character survey instrument was developed, consisting of 38 items. The results of the Exploratory Factor Analysis (EFA) indicated that 32 items were valid for measuring six aspects of students' P5 character. Content validity was tested using Aiken’s V formula, yielding high scores, while the instrument’s reliability was estimated using Cronbach’s Alpha, indicating high reliability. The evaluation results showed that in the readiness stage (antecedent), the human resources (HR) aspect scored 83% (very good) and the tools and materials aspect scored 75% (good). In the process stage (transaction), program implementation reached 90% (very good), while in the outcome stage, the program results scored 87% (very good), and the student character survey scored 81% (very good). These findings indicate that the implementation of P5 in elementary schools has been carried out very well, although improvements are still needed in certain areas. The study recommends facilitator training, enhanced understanding of the role of human resources, and continuous government supervision and support to optimize the implementation of P5.